Pendidikan Agama Islam sebagai Instrumen Peningkatan Moralitas Untuk Mendukung Pemberantasan Korupsi - Baiq Mulianah (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
This study aims to: 1) Analyze the contribution of Islamic religious education in fostering individual morality to prevent corrupt behavior, 2) Assess the role of Islamic religious education in supporting efforts to eradicate corruption in Indonesia. The study uses a literature study method, with data collection through primary and secondary data, as well as data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic religious education has a strategic role in shaping individual morality through internalizing the values ​​of honesty, responsibility, justice, and integrity. These values ​​equip individuals with ethical awareness to reject corrupt practices, both in personal life and social interactions, and foster sustainable anti-corruption behavior. In addition, Islamic religious education also contributes to strengthening the anti-corruption culture at the social and institutional levels, encouraging the creation of collective norms that reject corruption, strengthening integrity in decision-making, and supporting the creation of an ethical society and a clean, accountable, and just government system. This study emphasizes the importance of Islamic religious education as a strategic instrument in eradicating corruption in Indonesia.